Günümüz Türkiye’sinde hıristiyanlaşma ve Türk misyonerler - Sevinç, Bayram (My University, 2005)
Günümüz Türkiye'sinde dinsel dönüşüm ve misyonerlik, toplumsal refleksler için önemli unsurlardandır. Dinsel dönüşüm olaylarına yönelik ortaya çıkan tepki ve anlama çabaları çoğunlukla misyonerlik çerçevesindedir. Bu eğilim, dinsel dönüşüm yaşayan bireyin bu deneyimini ihmal etmiştir. Bu çalışmada, Hıristiyanlık yönünde dinsel dönüşüm yaşayan bireylerin bu deneyimleri ve olası sonucu olarak misyonerlik incelenmiştir. Bu araştırmada mülakat, doküman incelemesi ve gözlem tekniğiyle elde edilen veriler, içerik analizi ve betimsel analiz yoluyla irdelenmiştir. Bu araştırmada; anlamsızlık hissi, etkili sosyal bağlar, yoksunluklar, evlilik, davranışları referans alma, sosyalizasyon sorunu, ergenlik, kimlik krizi, misyonerlik, referans grubu, aile ilişkileri, kriz, geçmişinden kopma arzusu ve teolojik sorgulamalar, dinsel dönüşüm nedenleri olarak tespit edilmiştir. Öte yandan, dinsel dönüşüm yaşayan bireylerin yeni dinsel kimliğinin, yaşamlarında kaplayıcı bir şekilde etkin olduğu tespit edilmiştir. Name and Surname: Bayram Sevinç Field : Theology Programme: The Sociology of Religion Supervisor: Doç. Dr. M. Tayfun Amman Degree Awarded and Date: Master - July 2005 Religious conversion, missionary, religious change

THE CHRISTIANIZATION AND TURKISH MISSIONARIES IN CONTEMPORARY TURKEY The religious conversion and proselytizing are important for social reflexes in contemporary Turkey. The zeal of understanding and reaction that emerged towards religious conversion events are mostly in the frame of proselytizing. This tendency, neglected the experience of converts. In this study, the experience of converts who converted to Christianity and proselytizing as its probable result are investigated. In this research, the datum that obtained by interview, observation and documentation techniques is examined by content and descriptive analysis. In this research, sense of meaningless, effective social bonds, deprivations, marriage, taking behaviors as a reference, socialization problem, adolescence, identity crisis, proselytizing, reference group, family relationship, crisis, the desire to get rid of the past and theological investigations are discovered as causes of religious conversion. On the other hand, it is discovered that the new religious identity of converts is pervasively effective.
Keywords: Misyonerlik